Predicting and analyzing the performance of biomass-burning natural draft rocket cookstoves using computational fluid dynamics. (December 2019) - Pundle, Anamol; Sullivan, Benjamin; Means, Paul; Posner, Jonathan D.; Kramlich, John C.
Abstract: Nearly three billion people in the world today rely on biomass for their cooking needs. Indoor cooking using biomass has been identified as a major cause of respiratory illnesses, resulting in four million premature deaths every year. Improved biomass cookstoves may help mitigate this challenge. This paper presents a two-dimensional axisymmetric steady-state computational fluid dynamics (CFD) model of a biomass burning, natural draft rocket cookstove. The CFD model includes coupled sub-models representing combustion, turbulence, and heat transfer. The model is validated against experimental data and used to predict temperatures and flow inside the cookstove, including the airflow rate through the cookstove and heat transfer to the cookpot. We find that the excess air is typically many times stoichiometric air during standard operating conditions and is sensitive to flow field obstructions. We analyze the effects of geometric and operational features such as the pot support height, secondary air entrainment, cone-deck shape, and baffle placement within the cookstove on the flow, airflow rate, mixing, and stove thermal efficiency. The model shows that secondary air entrainment, though ineffective by itself, increases turbulent mixing when used in conjunction with a central baffle but reduces thermal efficiencies due to enhanced heat transfer to the walls. We find that a lower pot support height decreases the airflow rate and increases thermal efficiency. We model thirty-six cone-deck configurations and find that the cone-deck shape primarily affects the airflow rate through the stove, with more constricted designs leading to higher thermal efficiencies. Highlights: A 2D axisymmetric model of a natural draft rocket cookstove is presented. The air mass flowing through the stove is many times combustion stoichiometry requirements. Air mass flow rate is relatively constant for firepowers between 2 and 5 kW. Cone-deck designs that constrict airflow lead to higher efficiency. Secondary air entrainment can result in improved mixing when combined with a baffle.